(untitled) (Journal of Global Humanities and Social Sciences, 2024)
The Chinese Spring Festival Rush Phenomenon (Spring Rush) is a focal reflection of contemporary China’s economic and social development. After the founding of the People’s Republic of China, industrialization began, the population of cities and industrial and mining areas increased, and the number of passengers during the Spring Festival increased. In 1954, the country first clearly defined the Spring Rush as a month before and after the Spring Festival, and the Spring Rush officially appeared. Due to the industrialization strategy and the dual urban-rural social structure caused by the identity society, social mobility gradually stagnated before the reform and opening up, and the overall passenger flow during the Spring Festival was not large, and the Spring Rush was not obvious. Since the reform and opening up, with the rapid development of industrialization and urbanization, identity barriers have gradually been broken, and the speed of social mobility has accelerated; however, the country’s investment in social construction focusing on household registration, employment, social security, and other systems is insufficient, making it difficult for migrant workers and other lower-class people in society to urbanize. Their "pendulum"-like the one-way flow of "returning to the countryside before the New Year and returning to the city after the New Year" has been repeated, and the Spring Rush has become more and more serious.